Mulheres em STEM: um estudo na perspectiva da carreira caleidoscópica - Vieira, Ticiana Hiluy (2024)
This study aims to understand how women in the STEM field develop their careers from a kaleidoscopic perspective. STEM, an acronym in English for “science, technology, engineering, and mathematics”, represents a system of scientific learning that brings together a set of knowledge from these areas, considered fundamental for the development of transversal skills such as critical thinking, creativity, problem-solving, and innovation in various sectors of society. It is a field still predominantly dominated by men, despite the gradual global increase of women in professions typical of these disciplines. Career and gender are interdisciplinary themes by nature. The kaleidoscope career model, created by Mainiero and Sullivan (2005), describes how individuals change the design of their careers and make professional decisions, considering the various facets of personal and family life, according to the parameters Authenticity, Balance and Challenge (ABC). The research was conducted in a national and international food industry, considering its scope, size, and number of employees, which allows for the investigation of female professionals in this area. A basic, descriptive, and exploratory interpretative qualitative study was conducted. The research involved 15 professionals from the chosen company. Interview data were analyzed using Bardin's content analysis (2011). The results indicate that the majority of the interviewed professionals demonstrate a solid alignment with the growth and/or balance parameters. Even in authenticity-related contexts, there were records in line with the concepts of growth and balance. It is remarkable how strong the responses based on the balance between work and personal life were, reflecting the fact that 77% of these professionals have children up to early childhood. For the institution under study, this study provides insights into actions that HR professionals and leaders can adopt to be more effective in terms of development and benefits for women in this area, such as flexibility-related benefits that encourage parenthood and development actions to boost career growth for this audience.